Precursor, catalyst and preparation method, carbon nanotube and preparation method
By using specific components and preparation methods in the catalyst precursor, the problems of insufficient catalyst activity and high metal residue in the prior art are solved, and high yield and high purity fish bone structure carbon nanotube production is achieved.
Patent Information
- Application Number
- CN202411517800.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The prior art has problems such as insufficient catalyst activity, excessive metal catalyst residues, and low product purity and application value in the production of fish bone structure carbon nanotubes, resulting in poor production efficiency and product quality.
A catalyst precursor is provided, including a main powder, a support powder, a surface modifier and a structure guide agent. Through specific component ratios and preparation methods, a highly active and selective catalyst is prepared for the growth of fish bone structure carbon nanotubes.
The yield and purity of carbon nanotubes in fish bone structure are improved, the residual amount of metal catalyst is reduced, the activity and selectivity of the catalyst is enhanced, and large-scale, high-quality and low-cost production is achieved.
Smart Images

Figure CN119034823B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a catalyst precursor, a catalyst and a preparation method thereof, a carbon nanotube and a preparation method thereof. Background Art
[0002] In the process of pursuing large-scale production of fishbone structure carbon nanotubes, the existing technologies mainly use catalytic chemical vapor deposition and solvent thermal autoclave catalytic pyrolysis. Among them, the catalytic method has the problems of insufficient catalyst activity and excessive metal catalyst residue. At the same time, a large number of ordinary carbon nanotubes and carbon impurities are mixed in the product, which significantly reduces the purity and application value of the product.
[0003] In summary, the production technology of fishbone carbon nanotubes has significant deficiencies and challenges in terms of yield, purity, safety and industrial application. Therefore, future research should focus on developing more efficient, stable and economical catalyst systems, exploring more suitable carbon sources and reaction conditions, and optimizing the production process to achieve large-scale, high-quality and low-cost production of fishbone carbon nanotubes. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention provides a catalyst precursor, a catalyst and a preparation method thereof, a carbon nanotube and a preparation method thereof.
[0005] In order to achieve the above object, as a first aspect of the present invention, a catalyst precursor is disclosed, and the catalyst precursor comprises:
[0006] A main body powder, wherein the main body powder comprises a plurality of main body particles, and the main body particles contain a transition metal element;
[0007] Carrier powder, the carrier powder comprising a plurality of carrier particles, the specific surface area of the carrier particles being greater than the specific surface area of the main particles;
[0008] A surface modifier, wherein the surface modifier contains tin;
[0009] and a structure directing agent, wherein the structure directing agent comprises a high molecular organic compound having an adsorption function.
[0010] Furthermore, the structure directing agent includes a shape directing agent.
[0011] Furthermore, the structure directing agent comprises polyvinyl pyrrolidone with multiple degrees of polymerization.
[0012] Furthermore, the weight of the metal element in the main powder is 20% to 70% of the weight of the carrier powder, the weight of the tin in the surface modifier is 5% to 20% of the weight of the carrier powder, and the structure directing agent is 5% to 30% of the weight of the carrier powder.
[0013] Furthermore, the surface modifier is selected from at least one of elemental tin, tin oxide and tin salt.
[0014] Furthermore, the carrier particles include porous materials.
[0015] Furthermore, the carrier particles are selected from at least one of magnesium compounds, aluminum compounds, silicon compounds, titanium compounds, barium compounds and calcium compounds.
[0016] Furthermore, the catalyst precursor further comprises a dispersant, and a molar ratio of the metal in the catalyst precursor to the dispersant is in the range of 1:1 to 10:1.
[0017] Furthermore, the catalyst precursor also includes a co-catalyst, and the weight of the metal element in the co-catalyst is 2% to 15% of the weight of the carrier powder.
[0018] As a second aspect of the present invention, a method for preparing a catalyst is disclosed, the preparation method comprising:
[0019] Mixing the catalyst precursor and water to obtain a mixed solution;
[0020] Dehydrating the mixed solution to obtain an initial catalyst;
[0021] The initial catalyst is crushed, calcined, and then crushed again to obtain the catalyst.
[0022] Further, the dehydration treatment of the mixed solution comprises:
[0023] The mixed solution is heated and stirred, the heating and stirring temperature is between 60° C. and 100° C., and the heating and stirring time is between 1 hour and 24 hours.
[0024] Furthermore, in the step of mixing the catalyst precursor with water to obtain a mixed liquid, the concentration of the structure directing agent in the mixed liquid is between 0.05 wt% and 2 wt%, the concentration of the main powder in the mixed liquid is between 15 wt% and 35 wt%, and the concentration of the surface modifier in the mixed liquid is between 1.7 wt% and 4.1 wt%.
[0025] Furthermore, in the step of crushing the initial catalyst, calcining it and then crushing it again to obtain the catalyst, the calcination temperature is between 400° C. and 700° C., and the calcination time is between 0.5 hour and 3 hours.
[0026] As a third aspect of the present invention, a catalyst is disclosed. The catalyst is prepared by the above-mentioned preparation method.
[0027] As a fourth aspect of the present invention, a method for preparing carbon nanotubes is disclosed, comprising:
[0028] The catalyst is heated to between 680° C. and 750° C., and a carbon source gas is introduced to react to obtain initial carbon nanotubes, wherein the catalyst is the above-mentioned catalyst;
[0029] The initial carbon nanotubes are cooled to room temperature to obtain the carbon nanotubes.
[0030] Furthermore, the carbon source gas includes ethylene and / or propylene.
[0031] As a fifth aspect of the present invention, a carbon nanotube is disclosed, which is prepared by the above-mentioned preparation method.
[0032] The present invention has the following beneficial effects:
[0033] The invention provides a catalyst precursor, aiming at improving the purity and yield of fishbone carbon nanotubes.
[0034] The main body powder is used to prepare the catalytic metal particles of the subsequent catalyst. The powder shape is conducive to uniform dispersion in the liquid during the subsequent preparation of the catalyst to prevent agglomeration. The main body powder includes a plurality of main body particles, which are precursor particles for the subsequent preparation of the catalytic metal particles. The main body particles contain transition metal elements. The stability of the transition metal in the metal phase or alloy is higher under the carbon atmosphere, which can avoid the formation of more metal carbide phases, thereby promoting the rapid diffusion of carbon in the catalytic metal particles, and precipitating from the surface of the catalytic metal particles to grow into carbon nanotubes, thereby promoting the efficient growth of fishbone structure carbon nanotubes;
[0035] In addition, the carrier powder is also conducive to mixing and uniform dispersion. The specific surface area of the carrier particles is greater than the specific surface area of the main particles. After the main particles are prepared to form catalytic metal particles, the carrier particles can load the catalytic metal particles and disperse multiple adjacent catalytic metal particles to form gaps to prevent the catalytic metal particles from agglomerating. The catalytic metal particles have more surface area, thereby increasing more active sites for the growth of carbon nanotubes and improving the activity and growth efficiency of the catalyst.
[0036] On the other hand, a surface modifier is introduced. The surface modifier contains tin element. During the catalyst preparation process, tin can interact with the transition metal in the main particles, thereby affecting the interfacial growth of the prepared catalytic metal particles, so that more adjacent interfaces of the catalytic metal particles form angles, that is, the cross-section of the catalytic metal particles is polygonal. This morphological transformation is the core of the generation of fishbone structure carbon nanotubes. Subsequently, carbon atoms dissolve and diffuse in the catalytic metal particles, and precipitate on two adjacent interfaces to form graphite sheets with conical or stacked structures, and then stack multiple layers of graphene layers with conical structures along the crystal growth direction to form carbon nanotubes with fishbone structures, and the direction of the graphene sheets intersects with the direction of the carbon nanotube fiber axis; the surface modifier can also modify the surface structure of the internal catalytic metal particles during the catalyst growth carbon nanotube stage to form more catalytic metal particles with adjacent interfaces forming angles, that is, catalytic metal particles with polygonal cross-sections, rather than the common circular or elliptical cross-sections;
[0037] By using a structure directing agent, through its selective adsorption characteristics, it is possible to control the growth rate of each crystal face of the catalytic metal particles, thereby achieving the shaping of the cross-sectional shape of the catalytic metal particles.
[0038] This combination of catalyst components and the introduced structure-directing agent together construct a catalytic system that can maintain high activity and high selectivity in a high-temperature environment, providing a solid guarantee for the high-yield preparation of fishbone-structured carbon nanotubes.
[0039] Compared with traditional catalysts, in the catalyst prepared from the catalyst precursor of the present invention, the supported and dispersed catalytic metal can provide more active sites for reaction generation, so that the catalytic efficiency is improved, and the set amount of catalyst can be transformed into more carbon nanotubes, avoiding excessive metal and other impurities from remaining, showing higher activity, and the catalyst of the present invention can grow to form a large number of special fishbone structure carbon nanotubes rather than ordinary carbon nanotubes and has higher selectivity, thereby enabling the present invention to abandon the high-activity acetylene carbon source that easily triggers polymerization reaction in the process of preparing carbon nanotubes, and instead use ethylene or propylene as an alternative carbon source. This change avoids the generation of a large amount of tar by-products, and also overcomes the problem of low yield of generated carbon nanotubes due to the lower activity of ethylene or propylene than acetylene.
[0040] The catalyst preparation method of the present invention comprises mixing the above-mentioned catalyst precursor with excess water and stirring continuously to uniformly disperse the components in the catalyst; the heating and stirring are provided in order to hydrothermally dissolve the insoluble catalyst carrier at high temperature to further uniformly disperse the catalyst components, and the catalyst uniformly dispersed by the preparation method of the present invention also makes the load, catalytic metal particles, surface modifier and structure directing agent more evenly distributed, avoiding large agglomeration so that the catalyst has higher catalytic activity, and in the process of reacting with the carbon source to form carbon nanotubes, the catalytic metal particles are less likely to agglomerate and affect the activity of the catalyst.
[0041] When the catalyst of the present invention is used to synthesize carbon nanotubes, high-yield and high-purity fishbone structure carbon nanotubes can be obtained.
[0042] In summary, the catalyst precursor of the present invention not only solves the problems of low activity, poor selectivity, and many by-products existing in traditional catalysts, but also opens up a new way to achieve large-scale, high-quality production of fishbone structured carbon nanotubes.
[0043] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and drawings. The best embodiments or means of the present invention will be described in detail in conjunction with the drawings, but they are not intended to limit the technical solutions of the present invention. In addition, there are multiple features, elements, and components that appear in each of the following texts and drawings, and different symbols or numbers are marked for convenience, but they all represent components with the same or similar structures or functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The present invention will be further described below in conjunction with the accompanying drawings:
[0045] Figure 1 A schematic diagram of an embodiment of the catalyst precursor provided by the present invention;
[0046] FIG. 2 (a) is a schematic structural diagram of an embodiment of the catalyst provided by the present invention for catalyzing metal particles to grow fishbone structure carbon nanotubes;
[0047] FIG2( b ) is a schematic structural diagram of an embodiment of growing carbon nanotubes from conventional metal particles in a conventional catalyst;
[0048] Figure 3 A schematic structural diagram of an embodiment of the catalyst provided by the present invention in which the carrier particles support the catalytic metal particles;
[0049] Figure 4 A flow chart of an embodiment of the catalyst preparation method provided by the present invention;
[0050] Figure 5A flow chart of an embodiment of the method for preparing fishbone structure carbon nanotubes provided by the present invention;
[0051] Figure 6 is a transmission electron microscope photograph of the catalyst in Example 1 of the present invention;
[0052] Figure 7 This is a scanning electron microscope photograph of the fishbone structure carbon nanotube in Example 1 of the present invention.
[0053] Description of Reference Numerals
[0054] 1: Catalyst precursor 1a: Main particles
[0055] 1b: Carrier particles 1c: Surface modifier
[0056] 1d: Structure-directing agent
[0057] 11: Catalytic metal particles 12: Fishbone structure carbon nanotubes
[0058] 13: Carrier particles
[0059] 21: Conventional metal particles 22: Carbon nanotubes DETAILED DESCRIPTION
[0060] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments in the implementation manner are intended to be used to explain the present invention and should not be construed as limiting the present invention.
[0061] References to "one embodiment" or "example" or "example" in this specification mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment disclosed herein. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.
[0062] Carbon nanotubes are one-dimensional tubular nanomaterials formed by curling single or multiple layers of graphene, and have many outstanding physical and chemical properties. Its unique nanoscale diameter and rich pore network structure have brought significant performance improvements to lithium-ion battery technology. These pore structures build high-speed channels for lithium ions to shuttle between them, greatly promoting the insertion and deintercalation rate of lithium ions in the charge and discharge cycle, and significantly improving the rapid response capability and charge and discharge performance of lithium-ion batteries. The electrochemical properties of carbon nanotubes are complexly affected by their morphology, degree of graphitization, pore structure, and internal graphite sheet stacking mode. These factors are intertwined and jointly shape the conductivity of carbon nanotubes, the number of lithium ion embedding sites, and the kinetic process of lithium ion embedding / extraction. It is particularly worth mentioning that the carbon nanotubes with a unique fishbone structure have graphite sheets on the tube wall that are not arranged parallel to the tube axis, but tilted at a certain angle. This structure exposes more lithium ion embedding sites on the surface of the carbon tube, and greatly shortens the lithium ion migration path, making the lithium ion deintercalation process smoother and more efficient. This unique property gives lithium-ion batteries the potential and practical application value in meeting the challenges of high-current rapid charging and discharging.
[0063] Some carbon nanotubes with specific morphologies have a fishbone-like graphite sheet stacking structure inside. This unique microstructure is reflected in materials such as bamboo-shaped carbon nanotubes, spiral carbon nanotubes and quadrilateral carbon nanotubes. The test results of electrochemical properties show that these fishbone-structured carbon nanotubes exhibit electrochemical rate performance far superior to ordinary carbon nanotubes, bringing new hope to the field of energy materials. However, in the pursuit of large-scale production of fishbone-structured carbon nanotubes, the current preparation process - catalytic chemical vapor deposition and solvent thermal autoclave catalytic pyrolysis, has encountered bottlenecks. The main reason is that the developed catalyst system is not active enough and is accompanied by the problem of excessive metal catalyst residue, which greatly limits the production efficiency and product purity, and thus affects its promotion in large-scale continuous production and practical applications. On the other hand, the existing technology uses acetylene as a carbon source to indirectly improve the activity of the catalyst, which is accompanied by a large amount of tar generation. These tars cover the surface of the catalyst, accelerate the deactivation of the catalyst, and easily cause the reactor to be blocked, increasing the difficulty of equipment maintenance and cleaning, and seriously hindering its transformation process to industrial production. Therefore, improving the activity and efficiency of the catalyst, reducing the residual amount of metal catalyst, and finding alternative cleaning methods to achieve efficient, low-cost, and large-scale production of fishbone structured carbon nanotubes have become urgent issues to be addressed.
[0064] As a first aspect of the present invention, a catalyst precursor is provided, the catalyst precursor comprising:
[0065] Main body powder, the main body powder includes a plurality of main body particles, and the main body particles contain transition metal elements;
[0066] Carrier powder, the carrier powder includes a plurality of carrier particles, and the specific surface area of the carrier particles is greater than the specific surface area of the main particles;
[0067] Surface modifier, the surface modifier contains tin element;
[0068] and structure directing agents, which include high molecular organic compounds with adsorption function.
[0069] The shapes, sizes, proportions, angles, quantities, etc. disclosed in the drawings used to explain the catalyst precursors of the present invention are exemplary, and the present invention is not limited to the contents shown. For example, although the catalyst precursors are represented by round particles in the drawings, it does not mean that the actual catalyst precursors are a combination of round particles, and the size, position, structure, etc. of the different round particles shown in the drawings are intended to be used to explain the present invention, and the present invention is not necessarily limited to the above parameters shown.
[0070] A schematic diagram of a catalyst precursor of the present application is as follows: Figure 1 As shown, the catalyst precursor 1 includes a main powder, which includes a plurality of main particles 1a, and the main particles contain transition metal elements; a carrier powder, which includes a plurality of carrier particles 1b, and the specific surface area of the carrier particles 1b is greater than the specific surface area of the main particles 1a; a surface modifier 1c, which contains tin elements; and a structure directing agent 1d, which includes a high molecular organic compound with adsorption function.
[0071] The main powder is used to make catalytic metal particles in the catalyst. The powder form is conducive to uniform mixing and dispersion in the liquid during the preparation of the catalyst to prevent agglomeration. The main powder is composed of main particles. The main particles are precursor particles for the subsequent preparation of catalytic metal particles. The size, morphology, interface characteristics, metal components and other properties of the catalytic metal particles play a key role in the nucleation growth and structural regulation of carbon nanotubes. The catalytic metal is made of transition metal materials and is made into catalytic metal particles. The main particles contain transition metal elements. The transition metal contacts and reacts with the carbon source at high temperature to maintain the stability of the metal phase or alloy and avoid the formation of more metal carbide phases, thereby promoting the rapid diffusion of carbon in the active metal particles and promoting the efficient growth of fishbone structure carbon nanotubes.
[0072] The present invention does not make any special restrictions on the selection of transition metals. The physicochemical properties of metal catalysts are essentially determined by their electronic structure. As a catalyst, the most important thing is the binding energy with carbon and the catalytic activity of cracking carbon precursors. On metal particles with high catalytic activity, hydrocarbon molecules can be catalytically decomposed at a lower temperature, and carbon nanotubes are more likely to grow. The catalytic activity mainly depends on the binding energy with carbon. The transition metal forms a bond with the outermost electrons of carbon through an empty d orbital. The more electrons are bound to the empty d orbital, the more stable the carbide is, and the higher the metal-carbon binding energy is. The transition metal of the present invention is not easy to bind too strongly to carbon. If the metal-carbon binding is too strong, a stable carbide is formed, which is a deep potential well in the reaction and growth process of carbon nanotubes. A higher temperature is required to precipitate carbon. However, if the binding energy is too low, the graphite sheets formed by carbon atoms are easily separated from the catalyst particles, and it is difficult to complete the nucleation growth of carbon nanotubes. Preferably, the transition metal element is selected from at least one of iron, cobalt and nickel. Iron, cobalt and nickel have the highest growth efficiency because they can form metastable carbides, and are relatively ideal choices for metal catalysts.
[0073] As an optional embodiment, the transition metal material can be selected from at least one of the metal elements, metal oxides and metal salts of the above-mentioned iron, cobalt and nickel metals. In some embodiments, the catalyst precursor can be at least one of iron salts, nickel salts and cobalt salts. The types of iron salts selected include but are not limited to ferrous chloride, ferric acetate and ferric nitrate, and the nickel salts include but are not limited to nickel nitrate, nickel sulfate and nickel acetate; cobalt salts include but are not limited to cobalt nitrate, cobaltous chloride and cobalt acetate. Preferably, the catalyst precursor is selected from at least one of ferric nitrate, cobalt nitrate and nickel nitrate having the same acid radical ions. The multi-component transition metal salt mixed solution has a high concentration, a large osmotic pressure, and a large amount of active catalytic metal components loaded on the carrier.
[0074] Preferably, the weight of the metal elements in the main powder is 20% to 70% of the weight of the carrier powder. As the weight ratio of the metal elements increases, the number of catalytic metal particles formed increases, which can provide more active growth sites for the fishbone structured carbon nanotubes. However, too much weight ratio of the metal elements will result in excessive residual metal and contamination of the product. Too low a ratio will also result in too few catalytic metal particles, resulting in less target product generated and low yield.
[0075] The carrier powder is also conducive to mixing and uniform dispersion during the subsequent preparation of the catalyst. The carrier powder includes a plurality of carrier particles. The specific surface area of the carrier particles is greater than that of the main particles. After the main particles are prepared to form catalytic metal particles, the carrier particles can carry a plurality of catalytic metal particles. Figure 3The figure shows a schematic diagram of an implementation method of carrier particles loading catalytic metal particles. The carrier particles 13 allow multiple adjacent catalytic metal particles 11 to be spaced apart so that the catalytic metal particles have more surface area to prevent the catalytic metal particles from agglomerating, thereby increasing more active sites for carbon nanotube growth and improving the activity of the catalyst and the yield of carbon nanotubes.
[0076] The present invention does not impose any special restrictions on the carrier, and it only needs to be a porous material and have a high specific surface area that can be used to load catalytic metal particles. Preferably, the carrier is selected from at least one of magnesium compounds, aluminum compounds, silicon compounds, titanium compounds, barium compounds and calcium compounds. For example, the carrier is selected from oxides, such as at least one of aluminum oxide, magnesium oxide, titanium oxide, silicon oxide, and calcium oxide. For another example, the carrier can also be selected from metal halides, such as magnesium chloride, aluminum chloride, etc. Preferably, the carrier is selected from a mixture of aluminum oxide powder and magnesium oxide powder, and the aluminum oxide powder is selected from γ-alumina.
[0077] The larger the specific surface area of the carrier powder, the stronger its loading capacity is, and it can load more catalytic metal particles, so that the catalytic reaction is more complete and the catalyst efficiency is higher. However, the specific surface area of the carrier should not be too large. Too large a specific surface area will cause the aggregation path of the catalytic metal particles to be too long, and they will not be able to aggregate to form particles of a specific size, thus making it impossible to grow carbon nanotubes. On the other hand, a carrier with too large a specific surface area will cause the catalytic metal to dissolve and form a solid solution or spinel, reducing the catalytic metal particles and lowering the yield of carbon nanotubes. Preferably, the specific surface area of γ-alumina is between 20 m2 / g and 200 m2 / g, and the specific surface area of magnesium oxide powder is between 20 m2 / g and 180 m2 / g.
[0078] The surface modifier contains tin element, which can interact with the transition metal in the main particles during the catalyst preparation process, thereby affecting the interfacial growth of the prepared catalytic metal particles. The structural schematic diagram of an embodiment of the catalytic metal particles growing fishbone structure carbon nanotubes in the catalyst provided by the present invention is shown in Figure 2 (a). The surface modifier of tin element makes the cross-section of more catalytic metal particles 11 polygonal, that is, more adjacent crystal planes of the catalytic metal particles 11 have an angle. This morphological change is the core of generating fishbone structure carbon nanotubes 12. Subsequently, carbon atoms dissolve and diffuse in the catalytic metal particles 11, and precipitate at the polygonal interface to form graphite sheets with a conical structure, and then stack multiple layers of graphene layers with a conical structure along the crystal growth direction to form fishbone structure carbon nanotubes 12, and the direction of the graphene sheets intersects with the direction of the carbon nanotube fiber axis.
[0079] The present invention does not specifically limit the material of the tin element. Preferably, the surface modifier is selected from at least one of elemental tin, tin oxide and tin salt. In some embodiments, the tin salt of the surface modifier is selected from stannous chloride.
[0080] The surface modifier can not only modify the surface structure of the internal catalytic metal particles during the catalyst preparation stage, but also can modify the surface structure of the internal catalytic metal particles during the catalyst growth stage of carbon nanotubes to form more catalytic metal particles with angles at adjacent interfaces, that is, catalytic metal particles with polygonal cross-sections, rather than the common circular or elliptical cross-sections. As shown in Figure 2 (b), a structural schematic diagram of an implementation method of growing carbon nanotubes from conventional metal particles in a conventional catalyst is shown, in which the cross-section of the conventional metal particles 21 is circular or elliptical. The carbon nanotubes grown by precipitating such a circular interface catalyst are just ordinary carbon nanotubes 22, and their graphene sheets are parallel to the direction of the carbon nanotube fiber axis. Metal particles of this morphology cannot form fishbone structure carbon nanotubes.
[0081] The surface modifier itself does not have catalytic activity. Preferably, the weight of tin in the surface modifier is 5% to 20% of the weight of the carrier powder. Too much surface modifier will make the carrier load more and thus affect and reduce the catalytic efficiency, while too little surface modifier will not be able to effectively interact with the catalytic metal, thereby controlling the morphology of the catalytic metal particles.
[0082] The structure directing agent can be used to control the growth rate of each crystal face of the catalytic metal particles through its selective adsorption characteristics, thereby achieving the shaping of the cross-sectional shape of the catalytic metal particles. Adsorbent organic polymer compounds have selective affinity for certain specific ions or molecules, allowing the two to combine. The adsorption principle can rely on the van der Waals force between molecules for adsorption, or it can be hydrolyzed to produce a hydrophilic network molecular structure for adsorption, or it can produce coordinated atoms or coordinated groups to react with specific metal ions to form coordinated bonds to achieve adsorption, or it can produce certain acidic or basic groups, which can be combined with cations or anions by electrostatic adsorption after dissociation in the solution.
[0083] The morphology of the catalytic metal particles of the present invention is particularly important and is the key to forming fishbone structured carbon nanotubes. The structure directing agent is preferably a shape directing agent, which is an organic ligand capable of guiding crystal growth. It dissolves to produce specific groups that complex with metal ions and adsorb and wrap on the formed metal crystal nuclei, thereby controlling the direction of crystal growth.
[0084] Preferably, the structure-directing agent includes a polymer of vinylpyrrolidone with multiple polymerization degrees. Polyvinylpyrrolidone (PVP) is a non-ionic polymer compound with amphiphilic properties, namely, a hydrophilic pyrrolidone part and a hydrophobic alkyl part. When mixed with the catalytic main powder and dissolved in a liquid, the main powder is hydrolyzed to produce metal ions. The pyrrolidone group in PVP has the ability to form a coordination bond with the metal ions. From a chemical point of view, the pyrrolidone group contains a nitrogen-containing five-membered ring structure, and these nitrogen-containing structures can form a coordination bond with the metal ions to form a complex. These ligand groups of PVP can react with many metal ions, including but not limited to iron ions, nickel ions, cobalt ions, and molybdenum ions. This complex reaction can adsorb metal ions and prevent metal ions from aggregating with each other. On the other hand, due to the strong repulsion of the hydrophobic alkyl in PVP in water, the distance between metal ions can be increased to prevent metal ions from aggregating with each other, thereby achieving a stable reaction system.
[0085] When PVP combines with catalytic metal ions to form coordination bonds, a large number of small crystal nuclei are formed at the beginning of the reaction; subsequently, PVP is adsorbed on the surface of the crystal and wrapped around the crystal, preventing the growth and agglomeration of the particles. The adsorbed crystal faces are passivated, and the crystal faces that are not adsorbed or wrapped can still grow freely, thereby affecting the morphology of the crystal face particles. On the other hand, because the amide structure of PVP can form intermolecular hydrogen bonds, the PVP molecules can be arranged in an orderly manner in the aqueous solution, so that the adsorbed crystal particles present an ordered structure.
[0086] As the concentration of PVP increases, the guiding and stabilizing effects on the metal crystal particles are enhanced, and the stability of the reaction solution is increased. However, too high a concentration is not conducive to the directional aggregation growth of metal crystal particles, because PVP is an amphiphilic molecule with a long organic chain, which is easy to form a network structure at high concentrations, and produces a multi-layer wrapping effect on the crystal particles, thereby affecting the directional growth of metal crystal particles in the solution. However, when the concentration of PVP is too low, the structural guiding effect on the metal crystal particles will be reduced, making the initially formed metal crystal particles easy to aggregate and precipitate, and uniform metal crystal particles cannot be obtained. Only at a suitable PVP concentration is it easier to obtain uniform, stable metal crystal particles with a specific morphology. Preferably, the structure-directing agent PVP is 5% to 30% of the weight of the carrier. In some embodiments, the model of PVP is K15 or K30.
[0087] The catalyst precursor also includes a dispersant, and the molar ratio of the metal to the dispersant in the catalyst precursor is in the range of 1:1 to 10:1. The addition of the dispersant plays a dual role: on the one hand, it can effectively adjust the pH value of the solution to ensure that the components coexist stably in a specific acidic environment; on the other hand, the dispersant can also form a stable complex with the metal ions in the solution. In the subsequent calcination process, this complexation can significantly slow down the aggregation rate of the catalytic metal particles, which is conducive to the formation of catalytic metal particles with uniform dispersion and fine particle size, thereby improving the overall performance of the catalyst. Preferably, the dispersant is selected from at least one of citric acid, tricarboxylic acid, mercaptosuccinic acid and succinic acid.
[0088] The catalyst precursor also includes a promoter. The weight of the metal element in the promoter accounts for 2% to 15% of the weight of the carrier. Preferably, the promoter is selected from molybdenum salts, and more preferably, the promoter is selected from ammonium heptamolybdate. In the process of preparing carbon nanotubes by the catalyst, a promoter molybdenum salt is added, which can efficiently capture the carbon source in the gas phase and transport it to the adjacent catalytic metal active sites, thereby greatly improving the activity of the catalyst.
[0089] As a second aspect of the present invention, a method for preparing a catalyst is disclosed, such as Figure 4 As shown, the following steps are included:
[0090] In step S110, the catalyst precursor is mixed with water to obtain a mixed solution;
[0091] In step S120, the mixed liquid is dehydrated to obtain an initial catalyst;
[0092] In step S130, the initial catalyst is crushed, calcined, and then crushed again to obtain a catalyst.
[0093] In step S110, the above-mentioned catalyst precursor is mixed with water to dissolve the components in the catalyst precursor. Water, as a solvent with relatively high solubility, can dissolve a large amount of the above-mentioned components in the solution. Even if some components are difficult to dissolve in water, preferably, excess water is added to increase the solubility to further disperse the catalyst precursor evenly. The present invention does not specifically limit the mixing method, and magnetic stirring, ultrasonic vibration, or heating stirring can be used.
[0094] Preferably, in the step of mixing the catalyst precursor with water to obtain a mixed solution, the concentration of the structure directing agent in the mixed solution is between 0.05wt% and 2wt%, the concentration of the main powder in the mixed solution is between 15wt% and 35wt%, and the concentration of the surface modifier in the mixed solution is between 1.7wt% and 4.1wt%. In some embodiments, the types of iron salts selected in the main powder include ferrous chloride, ferrous acetate and ferric nitrate, the nickel salts selected in the main powder include at least one of nickel nitrate, nickel sulfate and nickel acetate; the cobalt salts selected in the main powder include at least one of cobalt nitrate, cobaltous chloride and cobalt acetate; the molybdenum salt selected in the co-catalyst is ammonium heptamolybdate, and the surface modifier is tin salt selected as stannous chloride. If the concentration of the metal salt in the mixed solution is too low, it will lead to a long evaporation time, consuming energy and time costs, but if the concentration of the metal salt is too high, the catalyst mixed and dissolved unevenly. Preferably, the total concentration of metal salts in the mixed solution is between 0.2 g / mL and 0.5 g / mL. In some embodiments, the total concentration of metal salts in the mixed solution is 0.3 g / mL.
[0095] In step S120, the dehydration treatment can be carried out by heating and drying, or by natural evaporation, and the initial catalyst obtained is a mixed crystal after the mixed solution is dehydrated. Preferably, the dehydration treatment of the mixed solution includes: heating and stirring the mixed solution, the temperature of heating and stirring is between 60°C and 100°C, and the time of heating and stirring is between 1 hour and 24 hours. The purpose of setting the heating and stirring is to hydrothermally dissolve the insoluble components at high temperature to further evenly disperse the catalyst components, and the catalyst evenly dispersed by the preparation method of the present invention also makes the load, catalytic metal particles, surface modifiers and structure directing agents more evenly distributed, avoiding large agglomeration so that the catalyst has a higher catalytic activity, and in the process of reacting with the carbon source to form carbon nanotubes, the catalytic metal particles are less likely to agglomerate and affect the activity of the catalyst. Within this temperature range, the solubility of each component in water can be improved without denaturing the components.
[0096] In some embodiments, first, at least one of an iron salt, a nickel salt and a cobalt salt is dissolved in an appropriate amount of deionized water together with a molybdenum salt, a tin salt, citric acid and PVP to form a mixed solution of the desired concentration. Next, a certain amount of γ-alumina and a MgO carrier (or only one carrier) is added to the mixed solution and vigorously stirred for 2 hours at room temperature. After that, the mixed solution is gradually heated to a range of 60°C to 100°C, and reflux stirring is continued at this temperature for 1 hour. Subsequently, the condensation reflux is stopped, and stirring is continued until the water is completely evaporated. In the present invention, the water is evaporated by continuous stirring instead of conventional drying. This method can increase the dispersion of the components, which is conducive to the subsequent preparation of a more evenly dispersed catalyst. The purpose of reflux stirring is to avoid the solvent from volatilizing at high temperatures, thereby reducing the solubility of the above components in the solvent.
[0097] Preferably, in the step of crushing the initial catalyst, calcining and then crushing it, the calcination temperature is between 400°C and 700°C, and the calcination time is between 0.5 hours and 3 hours. By high-temperature calcination, impurities such as free carbon, sulfur, moisture, organic matter and other impurities can be removed and purified, and the initial catalyst formed can also be reduced to form catalytic metal particles. The crushing is to prevent the prepared catalyst from agglomerating, but to carry out catalytic reaction in a powder with a larger specific surface area, so that the catalysis can be more sufficient and the catalyst activity and efficiency can be improved. Preferably, the crushing process is carried out by high-speed shear crushing until the average particle size of the particles is less than or equal to 5.0 microns.
[0098] As a third aspect of the present invention, a catalyst is provided, which is prepared by the above-mentioned preparation method. When the catalyst of the present invention is used to synthesize carbon nanotubes, high-yield and high-purity fishbone structure carbon nanotubes can be obtained.
[0099] As a fourth aspect of the present invention, a method for preparing carbon nanotubes is disclosed, such as Figure 5 As shown, including:
[0100] In step S140, the catalyst is heated to between 680° C. and 750° C., and a carbon source gas is introduced to react to obtain initial carbon nanotubes;
[0101] In step S150, the initial carbon nanotubes are cooled to room temperature to obtain carbon nanotubes.
[0102] The carbon source gas can be at least one of ethylene and propylene. Compared with the traditional catalyst, in the catalyst prepared by the catalyst precursor of the present invention, the catalytic metals that are loaded and dispersed can provide more active sites for reaction generation, so that the catalytic efficiency is improved, and the set amount of catalyst can be transformed into more carbon nanotubes, avoiding excessive metal and other impurities from remaining, showing higher activity, and the catalyst of the present invention can grow to form a large number of special fishbone structure carbon nanotubes instead of ordinary carbon nanotubes and have higher selectivity, thereby making the present invention abandon the high-activity acetylene carbon source that is easy to induce polymerization reaction in the process of preparing carbon nanotubes, and use ethylene or propylene as an alternative carbon source. This change avoids the generation of a large amount of tar by-products, and also overcomes the problem of low yield of generated carbon nanotubes due to the lower activity of ethylene or propylene than acetylene.
[0103] Specifically, in a horizontal tube furnace reactor, the catalyst powder is evenly spread in a quartz boat. Then, under nitrogen protection, the temperature is gradually raised to a range of 680°C to 750°C. When the temperature is stable, ethylene or propylene gas is introduced as a carbon source. After reacting for 1 hour, the supply of the carbon source gas is turned off, and the mixture is naturally cooled to room temperature in a nitrogen atmosphere to prepare carbon nanotubes with a herringbone structure.
[0104] As a fifth aspect of the present invention, a carbon nanotube is provided, which is prepared by the above-mentioned preparation method, and the carbon nanotube is a fishbone structure carbon nanotube.
[0105] The present invention will be further described below in conjunction with preparation examples and embodiments.
[0106] Preparation Example
[0107] Preparation Example 1
[0108] A method for preparing a catalyst, comprising:
[0109] Weigh 14.8 g of main powder, 1.84 g of co-catalyst, 1.9 g of surface modifier, 0.5 g of structure directing agent, 14.6 g of dispersant, and 10 g of carrier powder, wherein the main powder is cobalt nitrate powder, the co-catalyst is ammonium heptamolybdate, the surface modifier is stannous chloride, the structure directing agent is PVP (K-30), the dispersant is citric acid, and the carrier powder is 100 m2 / g of γ-alumina powder;
[0110] The main powder, co-catalyst, surface modifier, structure directing agent, and dispersant were added to 62 mL of deionized water to form an initial mixture;
[0111] adding carrier powder to the initial mixture to obtain a mixed solution;
[0112] After stirring the mixture at room temperature for 2 hours, the temperature was gradually raised to 90°C, and refluxed and stirred for 1 hour at this temperature; the condensation reflux was stopped, and stirring was continued until the water was completely evaporated to obtain the initial catalyst; the initial catalyst was crushed and calcined in an air atmosphere at 600°C for 0.5 h. Finally, the calcined material was crushed again to obtain catalyst 1.
[0113] Preparation Example 2
[0114] The catalyst was prepared using the method provided in Preparation Example 1, except that the main powder was 18.1 g of ferric nitrate and 12.3 g of cobalt nitrate, 3.8 g of stannous chloride, γ-alumina powder had a specific surface area of 150 m2 / g, the structure directing agent was 1.8 g of PVP (K-15), 24 g of citric acid, and 120 mL of deionized water. The mixed solution was stirred at room temperature and then heated to 70°C. The calcination temperature was 550°C and calcined for 1 hour to obtain Catalyst 2.
[0115] Preparation Example 3
[0116] The catalyst was prepared by the method provided in Preparation Example 1, except that the main powder was 18.1 g of ferric nitrate and 12.4 g of nickel nitrate, 3.8 g of stannous chloride, γ-alumina powder had a specific surface area of 120 m2 / g, the structure directing agent was 2.7 g of PVP (K-15), 24 g of citric acid, and 120 mL of deionized water. The mixed solution was stirred at room temperature and then heated to 100°C. The calcination temperature was 500°C and calcined for 2 hours to obtain Catalyst 3.
[0117] Preparation Example 4
[0118] The catalyst was prepared using the method provided in Preparation Example 1, except that the main powder was 18.1 g of ferric nitrate and 12.3 g of cobalt nitrate, no co-catalyst ammonium heptamolybdate and structure directing agent were added, stannous chloride was 3.8 g, γ-alumina powder had a specific surface area of 150 m2 / g, citric acid was 21.9 g, deionized water was 114 mL, the mixed solution was stirred at room temperature and then heated to 70°C, the calcination temperature was 550°C, and calcination was performed for 1 hour to obtain Catalyst 4.
[0119] Preparation Example 5
[0120] The catalyst was prepared using the method provided in Preparation Example 1, except that the main powder was 18.1 g of ferric nitrate and 12.3 g of cobalt nitrate, no co-catalyst ammonium heptamolybdate was added, stannous chloride was 3.8 g, the gamma alumina powder had a specific surface area of 150 m2 / g, the structure directing agent was 1.7 g of PVP (K-15), citric acid was 21.9 g, and deionized water was 114 mL. The mixed solution was stirred at room temperature and then heated to 70°C. The calcination temperature was 550°C and calcined for 1 hour to obtain Catalyst 5.
[0121] Preparation Example 6
[0122] The catalyst was prepared using the method provided in Preparation Example 1, except that the main powder was 18.1 g of ferric nitrate and 12.3 g of cobalt nitrate, no structure directing agent was added, stannous chloride was 3.8 g, γ-alumina powder had a specific surface area of 150 m2 / g, citric acid was 24 g, deionized water was 120 mL, the mixed solution was stirred at room temperature and then heated to 70°C, the calcination temperature was 550°C, and calcination was performed for 1 hour to obtain Catalyst 6.
[0123] Preparation Example 7
[0124] The catalyst was prepared by the method provided in Preparation Example 1, except that the promoter ammonium heptamolybdate, the structure directing agent and the carrier powder were not added, 12.5 g of citric acid and 30 mL of deionized water were used, and the above composition was added into the above deionized water to form a mixed solution;
[0125] The mixed solution was gradually heated to 80°C and magnetically stirred at this temperature for 6 hours to form a uniform transparent sol;
[0126] The sol is evaporated and dehydrated at 110°C until a dry gel is formed;
[0127] The dry gel was calcined at 450°C for 3 hours to obtain Catalyst 7.
[0128] Preparation Example 8
[0129] The catalyst was prepared by the method provided in Preparation Example 1, except that the co-catalyst ammonium heptamolybdate and the carrier powder were not added, the structure directing agent was 0.3 g of PVP, the citric acid was 12.5 g, and the deionized water was 30 mL. The above composition was added into the above deionized water to form a mixed solution;
[0130] The mixed solution was gradually heated to 80°C and magnetically stirred at this temperature for 6 hours to form a uniform transparent sol;
[0131] The sol is evaporated and dehydrated at 110°C until a dry gel is formed;
[0132] The dry gel was calcined at 450°C for 3 hours to obtain Catalyst 8.
[0133] Preparation Example 9
[0134] The catalyst was prepared by the method provided in Preparation Example 1, except that no carrier powder was added, the structure directing agent was 0.3 g of PVP, the citric acid was 14.6, the deionized water was 30 mL, and the above composition was added into the above deionized water to form a mixed solution;
[0135] The mixed solution was gradually heated to 80°C and magnetically stirred at this temperature for 6 hours to form a uniform transparent sol;
[0136] The sol is evaporated and dehydrated at 110°C until a dry gel is formed;
[0137] The dry gel was calcined at 450°C for 3 hours to obtain Catalyst 9.
[0138] The contents of the catalyst components and preparation parameters in the preparation example are shown in Table 1 below.
[0139] Table 1
[0140]
[0141] Example
[0142] Example 1
[0143] A method for preparing carbon nanotubes, comprising:
[0144] Weigh 1 g of catalyst 1, spread it flat in a quartz boat, and load it into a horizontal tube furnace. Then, introduce nitrogen gas at a flow rate of 300 mL / min. Heat the catalyst to 700°C at a rate of 10°C / min. During the heating process, the flow rate of nitrogen gas remains constant. When the temperature stabilizes, introduce propylene gas at a flow rate of 300 mL / min. React for 1 hour to obtain initial carbon nanotubes.
[0145] After the reaction was completed, the propylene gas was turned off and nitrogen was continued to be introduced. Under the protection of nitrogen, the reactor was allowed to gradually cool to room temperature to obtain product 1.
[0146] Example 2
[0147] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 2 was used and the temperature was raised to 710° C. to obtain product 2.
[0148] Example 3
[0149] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 3 was used, the temperature was raised to 720°C, and when the temperature was stable, ethylene gas was introduced at a flow rate of 300 mL / min to obtain product 3.
[0150] Example 4
[0151] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 4 was used and the temperature was raised to 710° C. to obtain product 4.
[0152] Example 5
[0153] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 5 was used and the temperature was raised to 710° C. to obtain product 5.
[0154] Example 6
[0155] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 6 was used and the temperature was raised to 710° C. to obtain product 6.
[0156] Comparative Example 1
[0157] Carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 7 was used to obtain product 7.
[0158] Comparative Example 2
[0159] The carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 8 was used to obtain product 8.
[0160] Comparative Example 3
[0161] The carbon nanotubes were prepared by the same preparation method as in Example 1, except that catalyst 9 was used to obtain product 9.
[0162] The specific process parameters for preparing carbon nanotubes in the embodiments and comparative examples are shown in Table 2.
[0163] Table 2
[0164]
[0165] Test Case
[0166] Catalyst 1 was tested using an EOL JEM 2100 transmission electron microscope to obtain a microscopic morphology of the catalyst. Figure 6 As shown in FIG. 1 , the black area is the catalytic metal particle, and its cross section is an irregular polygon. The subsequent carbon nanotubes are formed and grown at such an interface to finally obtain the fishbone structure carbon nanotubes. The carbon nanotubes in Example 1 were tested using a FEI Inspect F50 scanning electron microscope. Figure 7 As shown, the microscopic morphology of carbon nanotubes was obtained. Figure 7 There are multiple irregularly arranged carbon nanotubes in the structure, and each carbon nanotube has multiple stacked fishbone structures.
[0167] The microstructure of the products prepared by the catalysts in the above embodiments and comparative examples was observed, and the fishbone carbon nanotubes, ordinary carbon nanotubes and amorphous carbon in the products were classified and their corresponding proportions were counted to obtain the approximate distribution and proportion of fishbone carbon nanotubes, ordinary carbon nanotubes and amorphous carbon in different products. The diameter and specific surface area of the fishbone carbon nanotubes were measured and counted, as shown in Table 3.
[0168] The carbon nanotubes prepared in the examples and comparative examples were tested for quality using an electronic scale to obtain corresponding quality data of the carbon nanotubes, as shown in Table 3.
[0169] Example 1 prepared 13 g of product 1. Almost no ordinary carbon nanotubes were observed in the product, and almost all of them were fishbone structure carbon nanotubes with a specific surface area of 200 m 2 / g, tube diameter: 10~30 nm, and the tube wall has a fishbone structure.
[0170] Example 2 prepared 20 g of product 2. Almost no ordinary carbon nanotubes were observed in the product, and almost all of them were fishbone structure carbon nanotubes with a specific surface area of 150 m 2 / g, tube diameter: 20~30 nm, and the tube wall has a fishbone structure.
[0171] Example 3 prepared 25 g of product 3. Almost no ordinary carbon nanotubes were observed in the product, and almost all of them were fishbone structure carbon nanotubes with a specific surface area of 100 m 2 / g, tube diameter: 20~40 nm, and the tube wall has a fishbone structure.
[0172] Example 4 prepared 10 g of product 4, in which, in addition to the fishbone structure carbon nanotubes, less than 5% of ordinary carbon nanotubes were mixed.
[0173] Example 5 prepared 10.5 g of product 5, which was almost entirely fishbone structure carbon nanotubes, and almost no ordinary carbon nanotubes were observed in the product.
[0174] In Example 6, 19 g of product 6 was prepared. In addition to the fishbone structure carbon nanotubes, the product also contained less than 5% of ordinary carbon nanotubes. The specific surface area of the fishbone structure carbon nanotubes was 150 m 2 / g, tube diameter: 20~30 nm, and the tube wall has a fishbone structure.
[0175] Comparative Example 1 prepared 0.9g of product 7, in which amorphous carbon and ordinary carbon nanotubes accounted for more than 20%. Comparative Example 2 prepared 1g of product 8, in which amorphous carbon and ordinary carbon nanotubes accounted for more than 20%. Comparative Example 3 prepared 5g of product 9, in which ordinary carbon nanotubes accounted for more than 20%.
[0176] Table 3
[0177]
[0178] Compared with Example 1, the catalysts in Comparative Examples 1 to 3 did not introduce a co-catalyst and a carrier γ-alumina. The experimental results show that the yields of these three comparative examples decreased significantly. Specifically, due to the lack of the barrier effect of the carrier, the catalytic metal particles are very easy to agglomerate under the reaction conditions, which directly leads to a sharp decrease in the activity of the catalyst, and then the conversion rate of propylene is significantly reduced, accompanied by the occurrence of undesirable polymerization reactions, and a small amount of tar by-products are generated. In addition, the proportion of carbon impurities and ordinary carbon nanotubes in the product has increased, further proving that the catalytic effect is not ideal.
[0179] Compared with Example 2, Example 3 changes the type of catalytic metal and increases the content of the structure directing agent. The mass of carbon nanotubes obtained per gram of catalyst increases, and the change in the catalytic metal composition promotes the improvement of the catalyst activity.
[0180] Compared with Example 2, the catalyst in Example 4 lacks the addition of a structure-directing agent and a promoter of molybdenum. This lack also has an adverse effect on the activity of the catalyst, which is manifested as a significant decrease in yield; however, after the introduction of the γ-alumina carrier in Example 4, the proportion of ordinary carbon nanotubes in the product is significantly reduced. This result further emphasizes the importance of structure-directing agents, promoters, and carriers in catalyst design. The carrier can improve the activity and selectivity of the catalyst, and the structure-directing agent can also improve the selectivity of the catalyst, so that the product forms more fishbone structure carbon nanotubes rather than ordinary carbon nanotubes, and the promoter synergistically improves the activity of the catalyst. It is further explained that Example 5 adds a structure-directing agent on the basis of Example 4, and the proportion of fishbone structure carbon nanotubes in the product is higher, and the yield is increased, indicating that the structure-directing agent effectively regulates the size and morphology of the catalytic metal particles, thereby improving the activity and selectivity of the catalyst. Example 2 and Example 6 also have the same verification results.
[0181] The data of Example 5 and Example 6 show that the carrier and the PVP structure directing agent jointly affect the selectivity of the catalyst. Specifically, the introduction of the carrier effectively inhibits the aggregation and excessive growth of the catalytic metal particles, thereby limiting the "side reaction" of the formation of ordinary carbon nanotubes. This effect enhances the role of the tin element in the surface modifier of the catalytic metal particles to a certain extent. However, the presence of the carrier cannot completely eliminate the generation of ordinary multi-walled carbon nanotubes. On this basis, the addition of the PVP structure directing agent, which closely cooperates with the tin element in the surface modifier of the catalytic metal particles, achieves control of the microstructure of the carbon nanotubes by precisely regulating the growth rate of each crystal face of the catalytic metal particles, thereby optimizing the selectivity of the catalyst, making the catalytic process more efficient and the target product purer.
[0182] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for preparing a catalyst, characterized in that: The preparation method comprises: mixing a catalyst precursor with water to obtain a mixed solution; Dehydrating the mixed solution to obtain an initial catalyst; The initial catalyst is crushed, calcined, and then crushed again to obtain the catalyst, wherein the calcination temperature is between 400° C. and 700° C., and the calcination time is between 0.5 hour and 3 hours; The catalyst precursor comprises: A main body powder, wherein the main body powder comprises a plurality of main body particles, wherein the main body particles contain a transition metal element, and the transition metal element comprises at least one of iron, cobalt and nickel; A carrier powder, the carrier powder comprising a plurality of carrier particles, the carrier particles being selected from at least one of a magnesium compound, an aluminum compound, a silicon compound, a titanium compound, a barium compound and a calcium compound, and the specific surface area of the carrier particles being greater than the specific surface area of the main particles; A surface modifier, wherein the surface modifier contains tin element, the surface modifier is selected from at least one of elemental tin, tin oxide and tin salt, the surface modifier is used to make adjacent crystal planes of catalytic metal particles of the catalyst prepared from the catalyst precursor have an angle, and the catalyst is used to prepare fishbone structure carbon nanotubes; and A structure directing agent, wherein the structure directing agent comprises a high molecular organic compound having an adsorption function, the structure directing agent comprises polyvinyl pyrrolidone, and the weight ratio of the surface modifier to the structure directing agent is between 1.4 and 3.8 A promoter, the promoter comprising a molybdenum salt, wherein the weight of the metal element in the promoter is 2% to 15% of the weight of the carrier powder; The weight of the metal element in the main powder is 20% to 70% of the weight of the carrier powder, the weight of tin in the surface modifier is 5% to 20% of the weight of the carrier powder, and the structure directing agent is 5% to 30% of the weight of the carrier powder.
2. The preparation method according to claim 1, characterized in that: The catalyst precursor further includes a dispersant, and a molar ratio of the metal in the catalyst precursor to the dispersant is in a range of 1:1 to 10:
1.
3. The preparation method according to claim 1, characterized in that: The dehydration treatment of the mixed solution comprises: The mixed solution is heated and stirred, the heating and stirring temperature is between 60° C. and 100° C., and the heating and stirring time is between 1 hour and 24 hours.
4. The preparation method according to claim 1, characterized in that In the step of mixing the catalyst precursor with water to obtain a mixed solution, the concentration of the structure directing agent in the mixed solution is between 0.05wt% and 2wt%, the concentration of the main powder in the mixed solution is between 15wt% and 35wt%, and the concentration of the surface modifier in the mixed solution is between 1.7wt% and 4.1wt%.
5. A catalyst, characterized in that The catalyst is prepared by the preparation method according to any one of claims 1 to 4.
6. A method for preparing carbon nanotubes, characterized in that: include: The catalyst is heated to between 680° C. and 750° C., and a carbon source gas is introduced to react to obtain initial carbon nanotubes, wherein the catalyst is the catalyst according to claim 5; The initial carbon nanotubes are cooled to room temperature to obtain the carbon nanotubes.
7. The preparation method according to claim 6, characterized in that: The carbon source gas includes ethylene and / or propylene.
8. A carbon nanotube, characterized in that: The method is prepared by the preparation method according to any one of claims 6 or 7.
Citation Information
Patent Citations
Method for preparing carbon nanotubes
CN112203978A